Lower Motor Neuron Facial Palsy Triggered by Podophyllum Resin: A Case Report of Facial Nerve Dysfunction Following Topical Application - Sharma, M.; Belbase, U. (Devdaha Medical Journal, 2024)
This case report presents an 18-year-old male who developed left-sided facial weakness, tearing, and incomplete eyelid closure after applying podophyllum resin to a wart. Clinical examination confirmed Lower motor neuron facial palsy, with no systemic illness or abnormalities in hematological tests. The patient was treated with oral prednisolone, leading to a full recovery within 28 days. Podophyllum resin, a topical agent with neurotoxic potential, is rarely associated with facial nerve palsy. This case highlights the importance of considering external factors, such as neurotoxic agents, in the differential diagnosis of lower motor neuron facial palsy and emphasizes the need for further research into non-idiopathic causes.